Level Crossing Sampling in Feedback Stabilization under Data-Rate Constraints - Kofman, E.; Braslavsky, J.H. (Proceedings of the 45th IEEE Conference on Decision and Control, 2006)
This paper introduces a novel event-driven sampled-data feedback scheme where the plant output samples are triggered by the crossings - with hysteresis - of the signal through its quantization levels. The plant and controller communicate over binary channels that operate asynchronously and are assumed to be error and delay-free. The paper proposes two systematic output feedback control design strategies. The first strategy consists in the digital emulation of a previously designed analog controller. The second strategy is a simple direct design that drives the plant state to the origin in finite time after a total transmission of 2n + 2 bits, where n is the order of the plant